Shaking Hands with Linto Baroe and Dara Baroe in a Marriage Party According to Dayah Scholars (Case Study of Suka Makmue District, Nagan Raya Regency): Berjabat Tangan Dengan Linto Baroe Dan Dara Baroe Dalam Pesta Perkawinan Menurut Ulama Dayah (Studi Kasus Kecamatan Suka Makmue Kabupaten Nagan Raya) - A. Gani, Burhanuddin; Friatna, Ida; Asnawi, Syukri (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
There are problems related to shaking hands during weddings in Suka Makmue District, Nagan Raya Regency, carried out by people who deviate from the Qur'an, Hadith and cleric opinions, namely people think shaking hands at weddings with linto baroe and dara baroe is something polite and civilized. Even though the scholars agree that shaking hands with non-mahrams is haram. The problems to be investigated in this study are first, how to shake hands between guests and brides linto baroe and dara baroe which was carried out in Suka Makmue sub-district, Nagan Raya district, secondly, how are the views of dayah scholars on the practice of shaking hands between guests with linto baroe and dara baroe at wedding party. This research uses a case study approach, which produces descriptive data in the form of written or spoken words from the people observed. Field research includes interviews and documentation obtained from the community and cleric in Suka Makmue sub-district. From the results of the study, the procession of shaking hands with guests has two processes, namely, firstly, the linto or dara baroe meets the guest to shake hands and the second the guest shakes hands with the bride and groom when the intat linto/dara baroe process is completed by approaching the bride and groom while giving gifts. The results of the study second, the fourth view of the dayah scholars regarding shaking hands with non-mahram guests has several opinions where the legal issue of shaking hands with non-mahram directly is haram, except for small children or the elderly who do not have the potential to cause negative effects (desire and lust). slander). The law of shaking hands between the opposite sex and non-mahram by using gloves or a legal cover (permissible) as long as it does not have the potential to cause lust and slander.